Safety and Efficacy of Deep Brain Stimulation (DBS) in Patients with Treatment-Resistant Depression (TRD): A Review - Białogłowski, Michał; Dąbrowska, Julia; Gęborys, Anna; Wojcieszak, Maja; Matuszewska, Julia; Miazga, Dominika; Mazurek, Katarzyna; Lambach, Jakub; Kutnik, Kacper; Woźnica, Weronika (Quality in Sport, 2026)
Deep Brain Stimulation (DBS) is a promising, though still experimental, treatment for treatment-resistant depression (TRD) in patients who have failed standard forms of pharmacotherapy. The main objective of this study is to comprehensively analyze the safety profile of this method in light of the latest scientific reports from 2019–2025. A review of the literature shows that the use of DBS is associated with the risk of technical complications (e.g., infections, equipment failure) and neuropsychiatric complications (e.g., hypomania, anxiety, impulsivity). It has been shown that a key risk factor is the lack of precision in the location of electrodes relative to individual white matter tracts, which undermines the validity of using universal anatomical coordinates. The paper presents evidence that the implementation of modern technologies, such as preoperative tractography and closed-loop stimulation systems, can significantly reduce the risk of adverse effects while maintaining therapeutic efficacy. The conclusions point to the need for a multidisciplinary approach to patient qualification and monitoring, using objective electrophysiological and behavioral biomarkers.